Development of a questionnaire to measure coping with chronic skin diseases - Stangier, U; Gieler, U; Ehlers, A (1998)
General measures of coping styles do not adequately assess specific problems in coping with chronic skin diseases. In the present study, a questionnaire was developed for this purpose. Clinical interviews and items from other questionnaires yielded a pool of 93 items. A sample of 442 patients with different skin disorders completed the questionnaire. Principal components analysis with varimax rotation suggested a 6-factor solution with a total of 51 items. The factor structure was largely replicated in a second sample of 166 patients with atopic dermatitis. The six factors were interpreted as follows: social anxiety and avoidance, vicious circle of itching and scratching, helplessness, anxious-depressive mood, impact on quality of life, information seeking. Internal consistencies of the six scales were very good to satisfactory, with Cronbach's α ranging from .93 to .62. Correlations with scales assessing depression, anxiety and social anxiety, and significant differences between subgroups with different skin disorders supported the construct validity. The satisfactory reliability and validity justify clinical application of the questionnaire.